2012
DOI: 10.2478/s11772-012-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion management in soft glass all-solid photonic crystal fibres

Abstract: The development of all-solid photonic crystal fibres for nonlinear optics is an alternative approach to air-glass solid core photonic crystal fibres. The use of soft glasses ensures a high refractive index contrast (> 0.1) and a high nonlinear coefficient of the fibres. We report on the dispersion management capabilities in all-solid photonic crystal fibres taking into account four thermally matched glasses which can be jointly processed using the stack-and-draw fibre technique. We present structures with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Dispersion in such all-solid photonic crystal fibers can be shaped by matching the composition of glasses, not only by manipulation of the geometrical parameters of the microstructure. We demonstrated that such photonic structures can realize broadband normal dispersion, flattened in the 1200-3000 nm range [12]. In this work we demonstrate fiber of an all-solid glass photonic structure, in which the SC spectrum generated with 120 fs pump pulses at 1360 nm covered an octave bandwidth from 900 to 1900 nm.…”
Section: Introductionmentioning
confidence: 85%
“…Dispersion in such all-solid photonic crystal fibers can be shaped by matching the composition of glasses, not only by manipulation of the geometrical parameters of the microstructure. We demonstrated that such photonic structures can realize broadband normal dispersion, flattened in the 1200-3000 nm range [12]. In this work we demonstrate fiber of an all-solid glass photonic structure, in which the SC spectrum generated with 120 fs pump pulses at 1360 nm covered an octave bandwidth from 900 to 1900 nm.…”
Section: Introductionmentioning
confidence: 85%
“…It is especially important to assure similar values of the thermal expansion coefficients and the characteristic temperatures. Such structures, designed specifically with coherent SC generation in mind, were first demonstrated by Buczyński and co-workers [48]. They had their core and lattice made of the commercially available F2 glass (Schott O, 3.63.…”
Section: Glass and Fiber Designmentioning
confidence: 99%
“…Interest in photonic crystal fibers (PCFs) has lasted for more than two decades since their invention in 1996 [1]. The possibility of dispersion characteristics’ modification by a proper design of the geometrical structure as well as high optical power density in the fiber core led to applications in nonlinear optics [2,3]. Pumping PCFs with high-energy pulses in the anomalous regime of dispersion results in soliton fission that broaden the spectrum of a pulse, due to specific nonlinear phenomena, leading to supercontinuum generation (SG) which can theoretically span several octaves in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%